Skins, scars, blankets and blood : a pictorial response to the tensions and conflicts that arise from the representation and the practice of Ulwaluko in contemporary South Africa - Sobopha, Mgcineni (Michaelis School of Fine Art, 2017)
Ulwaluko (the subject of this study) is a Xhosa male initiation or rite of passage normally marked by elaborate ritual ceremonies and authenticated by circumcision. Human longing for ritual is deep, and in our contemporary culture is often frustrated. As an artist working in such an environment, my close association with these 'visible experiences' or contradictions in life has been the source and stimulus of my creative impulse. Ulwaluko is very close to me and an intensely personal aspect of my history and experience. It forms part of my identity and I ascertain very little distance between it and myself, if there can be any. It should be understood that this study is not an anthropological analysis of the Xhosa society and their cultural practices. Rather, it is a combination of autobiography and social commentary in which emphasis on first-hand experience is of primary importance for better understanding of the subject studied. This subjective experience also provides the basis, both conceptual and emotional, of the theoretical and creative process of this body of work. This project premises itself on the contentious issues around ulwaluko as practised by the Xhosa society, with particular reference to communities in Engcobo and Cape Town, and the tension in the creative work is rooted in the conflict and debate around this subject. An attempt is made to examine the impact of colonialism in the displacing and disrupting of this traditional Xhosa cultural practice. Basically, this study is a visual response to and an exploration of the tensions and conflicts that arise from the practice of ulwaluko and its representation in contemporary South Africa. And more important, it is a reflection of the struggle and the affirmation of the self in relation to my work as an artist. However, due to the complexity and sensitivity of this subject, I cannot generalise my understanding and experience of ulwaluko to be that of every Xhosa. The Xhosa people are not a homogeneous group as has been often perceived and discussed in various European discourses that are now under severe criticism by contemporary theorists such as Edward Said. It is a fact that people are different individuals, with dissimilar life experiences. Explaining other people's beliefs and feelings in an objective manner can seem to ignore or does not necessarily take into account, the personal value of emotions, of the joys and sorrows, and even of the transformation of the participants in the practice analysed. In recent years the practice and the visual representation of ulwaluko in South African society, by both 'insiders' and 'outsiders, has stirred concerns and provoked heated moral debates.